Impact of Environmental Management on Competitive Advantage of Tunisian Companies: The Mediator Role of Organizational Culture - Mohamed Hamdoun; Mahmoud Zouaoui (International Review of Management and Marketing, 2017)
In recent decades, companies have incorporated the environmental concerns in their strategic and operational activities. Despite previous literature, the debate about the competitive benefits of environmental practices is still open. This paper examines the role of organizational culture in the contribution of environmental management to competitive advantage. Data collected from 108 Tunisian companies were analyzed using structural equation modeling. The findings reveal that environmental management has a positive impact on competitive advantage regarding costs and differentiation. Moreover, environmental management has a positive effect on organizational culture which contributes to costs and differentiation competitive advantages.